Hierarchically porous carbon nanofiber binder-free electrode for high-performance lithium–sulfur batteries - Xiao, Ming; Li, Ruixue; Dai, Yu; Yang, Ting (Frontiers in Energy Research, 2022)
It is still a challenge for lithium-sulfur (Li-S) battery to possess high sulfur utilization and excellent electrochemical performances due to the low electrical conductivity and dissolution of polysulfides. To resolve these issues, a free-standing sulfur host composed of hierarchically porous carbon nanofibers (HPCNFs) has been synthesized via electrospinning technology. The HPCNFs with an interconnected and porous structure can facilitate electron transfer and electrolyte penetration. The mesoporous in HPCNFs can provide high levels of sulfur loading and the micropores can inhibit shuttle effects of the sulfur cathode during discharge and charge process. After encapsulating high mass of sulfur (76.4 wt%, HPCNFs@S), the electrode was directly applied as cathode for the Li-S battery, which exhibited a high specific discharge capacity of 1145 mAh g−1 at 0.1 C (1 C=1675 mA g−1) and maintained 787 mAh g−1 after 150 charge/discharge cycles. This work provides a new insight into optimizing the electrochemical performance of Li-S battery.